A Plan for the reduction and ultimate extinction of the National Debt - Urquhart, William Pollard (Dublin Statistical Society, 1855)
The embarkation of England in a war; the failure of the anticipations at first indulged in by some parties, that this contest could be carried on out of the revenue of the country; the recent addition of sixteen millions to the national debt, and the probability of its progressive augmentation during every year of the continuation of hostilities, all tend to impart interest to the question, whether any means should be taken to provide for the reduction or ultimate extinction of the debts incurred in the prosecution of past and present wars ; and if so, by what means this object can best be effected.
Read December 17th, 1855
Keywords: National debt; Taxation; 314.15